Hubungan antara Persepsi Risiko dan Kepercayaan Masyarakat Terdampak terhadap Otoritas dalam Upaya Mitigasi Dampak Kabut Asap Riau - Nurul Aiyuda; - Koentjoro (Gadjah Mada Journal of Psychology (GamaJoP), 2016)
Mitigation is the effort to reduce the impact of haze. This study was aimed to examine the relationship between risk perception and trust of authorities toward the mitigation effort of haze impact in Riau. Trust of authorities in this study included the government, military, police and medical authorities. For this aim, hypothesis have been tested using data collected from a sample of 256 people affected by haze which taken by using purposive sampling. Data were collected using three scales; the mitigation scale, the risk perception scale and the trust scale. This study found that risk perception and trust of authorities were simultaneously related to haze impact mitigation with R square 0,108. Risk perception may affect the mitigation effort. In this research can be found that the citizen mitigation tends to be low, this is caused by low public perception in rating the risk of haze impact in Riau. This study also found that the military and medical authorities correlated with haze mitigation effort; however the trust in the government and police authorities had no relationship with haze mitigation effort in Riau.